2021
DOI: 10.2106/jbjs.20.00218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Revision Risk Based on Timing of Knee Arthroscopy Prior to Total Knee Arthroplasty

Abstract: Background: Knee arthroscopy may be performed prior to total knee arthroplasty (TKA) in patients with symptomatic degenerative knee changes that do not yet warrant TKA. The purpose of this study was to determine whether the time interval between knee arthroscopy and subsequent primary TKA is associated with increased rates of revision and certain complications following TKA. Methods: Data from 2006 to 2017 were collected from a national insurance databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
15
3
Order By: Relevance
“…Within the past several years, authors have attempted to identify the ideal delay interval between knee arthroscopy and subsequent TKA, if indicated, with many specifying within 6 months as an inflection point, whereby the rates of poor outcomes develop. 4,7,9 However, literature to date is not reflective of the current rates of knee arthroscopies and TKAs. 10 We sought to compare four, timebased cohorts of patients who received a TKA within 24 weeks of an ipsilateral knee arthroscopy, as compared with a control of patients who did not have prior history of knee arthroscopies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Within the past several years, authors have attempted to identify the ideal delay interval between knee arthroscopy and subsequent TKA, if indicated, with many specifying within 6 months as an inflection point, whereby the rates of poor outcomes develop. 4,7,9 However, literature to date is not reflective of the current rates of knee arthroscopies and TKAs. 10 We sought to compare four, timebased cohorts of patients who received a TKA within 24 weeks of an ipsilateral knee arthroscopy, as compared with a control of patients who did not have prior history of knee arthroscopies.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Prior knee arthroscopy before a TKA may accelerate the development of knee stiffness given the intraarticular nature of knee arthroscopies. 6,7,18 A 2015 report assessing the timing between knee arthroscopy and TKA found that patients who had a knee arthroscopy within 6 months of a TKA had nearly two times increased risk of developing postoperative stiffness, as compared with other time intervals. A recent report by Gu et al 7 also found worse post-TKA outcomes in patients who had a prior knee arthroscopy within 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many kinds of pathogens known to cause PJI. Gram-positive bacteria, especially staphylococcus, are the most common pathogens 3 , followed by Gram-negative bacteria. Although fungal PJIs are rare, they account for less than 1% of postarthroplasty infections.…”
Section: Introductionmentioning
confidence: 99%